PEMBERDAYAAN EKS PEKERJA SEKS KOMERSIAL DI PUSAT PELAYANAN SOSIAL KARYA WANITA (PPSKW) MATTIRODECENG KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The purpose of this study is to 1). knowing the strategy of empowering ex-commercial sex workers at the Social Service Center for Women's Work (PPSKW) Mattirodeceng Makassar City, 2). knowing the obstacles faced in empowering former commercial sex workers at the social service center for Women’s Work (PPSKW) Mattirodecenf Makassar City. This type of research is a qualitative research that uses descriptive analysis methods, researchers conduct in-depth observations and interviews with social workers and ex-commercial sex workers (clients), especially those related to the empowerment of ex-commercial sex workers at the Center for Social Work for Women (PPSKW) Mattirodeceng City Makassar, while the secondary data here are references from libraries, magazines, books so that they can complement the primary data. The results of this study indicate that: 1). The strategy for empowering ex-commercial sex workers at the Social Service Center for Women's Work (PPSKW) Mattirodeceng Makassar City, includes (a) the initial approach, in the form of orientation and consultation, identification, motivation and selection, (b) Sponsorship, in the form of registration, administration and placement, ( c) social rehabilitation, in the form of physical guidance, mental and spiritual guidance, social guidance and skills guidance, (d) Resocialization, in the form of business guidance and distribution guidance, (e) distribution, in the form of returning to the family, working as domestic workers, working according to skills in orphanages and open independent businesses, (f) further guidance, and (g) Termination.2). The obstacles faced in empowering former commercial sex workers at the Social Service Center for Women's Work (PPSKW) Mattirodeceng Makassar City, include: (a) not getting a good response from the client, and (b) not getting a good response from the community. The implications of this research are; 1). to provide good service so that clients do not return to being prostitutes after completing the service period. 2). The community in the client's environment should provide support and assistance to the client towards a better direction than before.